MEWUJUDKAN TERTIB PENGELOLAAN KEUANGAN MELALUI IMPLEMENTASI AKUNTANSI DASAR PADA RUKUN WARGA 06 DI KOTA BANDUNG - Sri Dewi Anggadini; Fina Afrilia Elmanda (Indonesian Community Service and Empowerment Journal (IComSE), 2022)
The application of accounting to Hamlet is financial management and decision making and long-term planning as a control tool in the Hamlet environment to avoid expenses outside of Hamlet's planning, even to know the obligations to other parties. On the other hand, there are still findings that Hamlet has not carried out optimal financial management. This activity has the objectives of: 1). Sharing knowledge and working together in helping to optimize financial management; 2). Motivate ability and competence in financial management related to the ability to prepare financial statements; 3). Utilization of information systems so that management is not dominated by manual recording hopes that obstacles can be minimized, especially Microsoft Excel software applications. In its implementation, the method used in the form of training on Hamlet's financial management accompanied by giving examples of how to plan the financial expenditures of an institution, in this case, is Hamlet, how to record the institution's finances, the implementation of the institution's financial management and the assessment/supervision of the institution's finances. Furthermore, training in empowering Hamlet administrators by providing financial management tutorials through the introduction of basic accounting. Related to Hamlet's problems, solutions are needed to increase knowledge of implementing financial management in Hamlet 06 Antapani Wetan Village. They provide knowledge by socializing the concept of financial management and financial reporting by conducting discussion sessions with Hamlet 06 administrators related to the pattern of financial use obtained from government revenues and dues and non-governmental organizations.